Larval surveillance and habitat characterization of dengue vectors in Tangkak, Johor, Malaysia - Ili Zawani Kamari,; Nazri Che Dom,; Mohd Yusmaidie Aziz,; Farah Ayuni Shafie,; Ahmad Razali Ishak, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Entomological surveillance based on larval surveys, provides vital information for dengue management. In addition, the knowledge on breeding habitat of Aedes species is crucial to provide better understanding of their population densities and distribution. The larval surveillance method was conducted in ten outbreak areas in Tangkak District, Johore, Malaysia. The larval surveillance indices; House Index (HI), Container Index (CI), and Breteau Index (BI) were evaluated to measure the density of Aedes mosquito population. Then, habitat characterization was analyzed by calculating the prevalence, productivity and efficiency of the collected container. Approximately 1163 houses were inspected in Tangkak District and 86 (7.4%) houses were classified as positive premise. The highest HI were found in Taman Sialang (HI: 25 %) meanwhile the highest CI was recorded at Taman Jalan Ong Siong (CI: 71.4%). Eight out of 10 localities were found exceed the BI threshold value of 5%. The highest BI was logged in Taman Sialang (BI: 70%). Ae. albopictus represent 58% of the collected larvae meanwhile another 42% was Ae. aegypti. Some of the most effective container that contribute to the Aedes breeding in the study area were CID2: Flower pot, CID3: Plastic scrap, and CID4: Pail, with the productivity of 30%, 27%, and 19.8%, respectively. However, only CID2 and CID3 indicate higher prevalence of Aedes larvae with container prevalence of 31.1% and 26.9% respectively. In overall, CID2 was found to be the most preferred container for Aedes breeding since this container record the highest container efficiency (CE) value of 9.6%. The findings of this study could assist the health authority in the early prevention and control of dengue outbreak in Tangkak, Johor.